Visual exploratory activity and practice design: Perceptions of experienced coaches in professional football academies - Eldridge, D.; Pocock, C.; Pulling, C.; Kearney, P.; Dicks, M. (International Journal of Sports Science & Coaching, 2023)
The aim of this study was to explore: (a) football coaches` perceptions of visual exploratory activity (VEA) and (b) the practice activities designed by coaches believed to develop VEA. Semi-structured interviews were conducted with nine coaches who held the UEFA A or B Licence in coaching football. All coaches worked in an English professional football club's academy and held different coaching positions. Thematic analysis of the data identified three themes: Importance of VEA, Development of VEA and Delivery of VEA (e.g., practice design, visual aids, technology and questioning). The interviews revealed that all coaches hold VEA as an integral part of player performance yet are unsure of how to develop this behaviour. They deemed that VEA should be developed at a young age to enable players to reach an elite level of performance. Despite these views, coaches did not feel that VEA should be a particular focus on individual sessions and believed the VEA behaviour would be drawn out from practices used by coaches. There was a range of activities (N = 33) discussed by the coaches when they were asked to draw and provide examples of practices that they would use to develop VEA. The percentage of planned practices that were deemed active decision-making activities (70%) was greater compared to non-active decision-making activities (30%). This study has implications for the planning and interventions coaches place on practices to develop VEA. Future research should consider investigating the impact different types of practice have on performers` VEA.